Effects of opioid-free propofol or remimazolam balanced anesthesia on hypoxemia incidence in patients with obesity during gastrointestinal endoscopy: A prospective, randomized clinical trial - Zhang, Keyao; Bao, Yuan; Han, Xue; Zhai, Wenshan; Yang, Yi; Luo, Meng; Gao, Fang (Frontiers in Medicine, 2023)
There are presently no consensuses on the optimal sedation strategy for obese patients during gastrointestinal endoscopy. This study aim to explore the effects of opioid-free propofol or remimazolam balanced anesthesia on hypoxemia incidence in patients with obesity. A total of 264 patients were randomized to remimazolam + esketamine group (group R) or propofol + esketamine group (group P). Anesthesia in group P was administrated by propofol, esketamine and in group R by remimazolam, esketamine. The primary outcome was: incidence of hypoxemia. Secondary outcomes were: the time to loss of consciousness (LoC) and to recovery; incidence of intraoperative and postoperative adverse reactions. We found the incidence of mild hypoxemia in group R was similar to that in group P (14.2% vs 11.5%, P=0.396). The incidence of severe hypoxemia in group R was significantly lower than Group P (4.2% vs 9.2%, P=0.019). The time to LoC in group R was longer than group P [Median (interquartile range, IQR): 53 s (45 - 61) vs 50 s (42 - 54), P=0.001]. The time to recovery from anesthesia in group R was less than group P [Median (IQR): 48 min (41 - 58) vs 55.5 min (46 - 67), P＜0.001]. There was no significant difference in the incidence of adverse events (P>0.05 for all). We concluded that compared with propofol combined with esketamine, remimazolam combined with esketamine can reduce the incidence of severe hypoxemia during gastrointestinal endoscopy in obese patients.